Compensated Cirrhosis and 20 mm Hg: A Point of No Return?. (5th December 2020) - Reverter, Enric; Ott, Peter
Abstract : Abstract: This editorial comments on the findings from the study by Jindal et al. recently published in The American Journal of Gastroenterology . Weaknesses and strengths of the study are presented, and potential therapeutic strategies for compensated cirrhotic patients with an HVPG ≥20 mm Hg are proposed.